(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
After our country gained independence, a number of legislative acts were adopted in Uzbekistan to regulate insurance activities. The rules on insurance are primarily stipulated in Article 48 of the Constitution of the Republic of Uzbekistan. According to it, the state takes measures to develop the healthcare system, its state and non-state forms, various types of medical insurance, and ensure the sanitary and epidemiological well-being of the population. This article analyzes the concept of republican executive authorities and public control in the legal regulation of insurance activities in the Republic of Uzbekistan.